MODELLING AND MEASUREMENT OF AIRCRAFT ENGINE EMISSIONS INSIDE THE AIRPORT AREA - Zaporozhets, Oleksander; Synylo, Kateryna (Proceedings of National Aviation University, 2015)
The paper is aimed to improve complex model “PolEmiCa” by taking into account basic properties of contaminants transport and dilution by exhaust gases jet from aircraft engine near the ground. Validation of complex model “PolEmiCa” was implemented on the basis of measurement campaign at International Athens airport and International Boryspol airport.